Scaling the Rwanda Smart Nkunganire System (SNS) fertilizer recommendation tool: A comprehensive report on awareness and capacity building initiatives - Ogunsanmi, T.; Mudereri, B.T.; Senge, M.; Rabourn, T.R.; Sartas, M.; Ampadu-Boakye, T.; Kihoro, E.; Kangethe, E.; Uzamushaka, S.; Kayumba, J.; Cyamweshi, A.R. (2024)
The Smart Nkunganire System (SNS) is a transformative agricultural tool designed to enhance the efficiency and sustainability of farming practices in Rwanda. The pilot phase of the SNS Fertilizer Recommendation Tool (SNS-FRT) deployment, conducted in Rubavu and Nyanza, mobilized over 6,200 farmers (38% female) which focused on improving farmers' access to essential inputs, agronomic knowledge, and decision-making tools. This pilot successfully engaged a wide range of stakeholders, including farmers, agro-dealers, extension agents, the Rwanda Agriculture and Animal Resources Development Board (RAB) and One Acre Fund (OAF), ensuring effective dissemination and adoption of the revised SNS curriculum.